Conceptual framework for ethical artificial intelligence development in social services sector - Seniutis, Miroslavas; Gružauskas, Valentas; Lileikiene, Angele; Navickas, Valentinas (Human Technology, 2024)
This research explores the domain of Artificial Intelligence (AI) for social good, with a particular emphasis on its application in social welfare and service delivery. The study seeks to establish a universal conceptual framework for ethically integrating AI into the social services sector, recognizing the sector's significant yet underexplored potential for AI utilization. The objective is to develop a comprehensive framework applicable to the ethical deployment of AI in social services, using Lithuania as a case study to illustrate its practicality. This involves analysing the political discourse on AI, examining its applications in social welfare, identifying ethical challenges, evaluating the digitalization progress in Lithuania's public services, and formulating guidelines for AI integration at various stages of delivering social services. Our methodology is rooted in document analysis, encompassing a thorough review of both normative and scientific literature pertinent to the ethical application of AI in social welfare. Key findings reveal that AI's anticipated positive impacts on diverse social and economic areas, as highlighted in political declarations, are being partially realized, as corroborated by scientific studies. Although the global application of AI in social welfare is expanding, Lithuania presents a unique case with its strategic planning gaps in this sector. The developed conceptual framework offers vital criteria for the ethical implementation of AI systems designed to be universally applicable to various stages of social services, accommodating different AI applications, client groups, and institutional environments.